A Phishing and Malware Link Detector Using Checkphish API - IQMAL HAZEEQ,; DR SHAMSUL KAMAL BIN AHMAD KHALID, (Applied Information Technology And Computer Science, 2025)
The Suspicious Link Detection Extension is a web-based tool designed to enhance online security by providing real-time URL safety checks to protect users from phishing scams, malware, and other potential internet threats. Developed with Node.js and integrated with the Checkphish API, the extension evaluates URLs based on various factors, including their structure, domain reputation, and other identifying characteristics. Unlike traditional URL-checking tools that rely on outdated databases or user-reported issues, this extension offers real- time analysis of links, ensuring that users receive the most up-to-date information about potential threats. The extension’s user-friendly interface is designed with non-technical users in mind, allowing anyone to easily input URLs and receive immediate feedback on whether the link is safe, suspicious, or potentially harmful. This makes it an ideal tool for individuals, educational institutions, and businesses concerned about cybersecurity, offering a simple and effective way to prevent users from visiting malicious websites. The tool aims to bridge the gap between complex cybersecurity measures and everyday internet users by providing an easy-to-use, real-time safety check, ensuring a moresecure browsing experience for everyone. By making security technology more accessible, this project strives to create a safer internet environment, particularly for those with limited technical knowledge.